2020
DOI: 10.31223/osf.io/x7v4e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unequal anthropogenic enrichment of mercury in Earth’s northern and southern hemispheres

Abstract: Remote northern (NH) and southern hemisphere (SH) lake sediment and peat records of mercury (Hg) deposition show a ×3 to ×5 Hg enrichment since pre-industrial times (<1880AD), leading to the common perception that global atmospheric Hg enrichment is moderate and uniform. Anthropogenic Hg emission in the NH is, however, approximately four times higher than in the SH. Here we reconstruct atmospheric Hg deposition to four remote SH peatlands and review sediment and peat Hg records from both hemispheres. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…The present‐day unremote sediments showed 2.9‐ to 25‐fold increases in THg relative to their respective pre‐industrial sediments. The present‐day remote sediments, without Laguna Negrilla, Peru, showed 1.3‐ to 5.1‐fold increases in THg, consistent with those reported from other lake sediment cores collected from remote regions (3–5 fold) (Amos et al., 2015; Engstrom et al., 2014; Fitzgerald et al., 2005, Li et al., 2020). Among the remote sediments, a reduction in THg (0.53‐fold) was observed in Laguna Negrilla, Peru (Figure 1a), consistent with the cessation of widespread historical mercury mining for pigment and precious metal extraction (1532–1821 AD) (Cooke et al., 2013).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The present‐day unremote sediments showed 2.9‐ to 25‐fold increases in THg relative to their respective pre‐industrial sediments. The present‐day remote sediments, without Laguna Negrilla, Peru, showed 1.3‐ to 5.1‐fold increases in THg, consistent with those reported from other lake sediment cores collected from remote regions (3–5 fold) (Amos et al., 2015; Engstrom et al., 2014; Fitzgerald et al., 2005, Li et al., 2020). Among the remote sediments, a reduction in THg (0.53‐fold) was observed in Laguna Negrilla, Peru (Figure 1a), consistent with the cessation of widespread historical mercury mining for pigment and precious metal extraction (1532–1821 AD) (Cooke et al., 2013).…”
Section: Resultssupporting
confidence: 87%
“…The mercury isotope ratios of the pre‐industrial sediments appear to reflect both natural and anthropogenic mercury delivered via atmospheric deposition and runoff from the adjacent watershed. Previous evaluations of anthropogenic mercury enrichments in sediment and peat cores have suggested that historical anthropogenic activities (since 1450 AD) such as Spanish colonial mercury and silver mining (Amos et al., 2015) as well as deforestation and biomass combustion (Li et al., 2020) have liberated substantial amounts of mercury into the atmosphere. The resultant Hg 0 would have accumulated within foliage prior to watershed runoff or deposited to lake sediments upon atmospheric oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern anthropogenic Hg emissions to air (2400 Mg a -1 ) outweigh natural Hg emissions (340 Mg a -1 ) by an order of magnitude. 1,2 Hg emissions are mostly in the form of gaseous elemental Hg (GEM), which has a long (3 months) atmospheric life-time against oxidation to divalent reactive Hg (RM) forms that include gaseous oxidized Hg (GOM) and particulate bound Hg (PBM). 3 RM is rapidly deposited to continental and marine ecosystems where microbial and abiotic activity transforms a fraction of inorganic Hg into the bioaccumulating and toxic methylmercury form.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the spatial distribution of Hg emissions, observations show higher atmospheric Hg 0 levels in the northern hemisphere compared to the southern hemisphere ( 9 ). Sediment and peat records of atmospheric Hg deposition also suggest a larger anthropogenic Hg enrichment in the northern hemisphere ( 10 ). Anthropogenic Hg emissions are thought to have tripled the concentrations of total Hg in the thermocline waters (100 to 1,000 m) of the global ocean relative to deeper older waters ( 11 ), yet still unclear is how these anthropogenic Hg inputs are converted into methylmercury in oceans.…”
mentioning
confidence: 99%